Hubungan Self-efficacy dengan Work Engagement pada Karyawan Pusat Pengembangan Anak (YCI) Selama Masa Pandemi Covid-19 - Kurnia Adi Mardiana; Sutarto Wijono (Kuras Institute, 2022)
This study aimed to determine the relationship between self-efficacy and work engagement of employees of the Child Development Center (YCI) cluster in Semarang Regency during the COVID-19 pandemic. The method used in this research is quantitative research with a correlation design. The participants in this study were 50 PPA cluster employees in Semarang Regency who felt the impact of working during the COVID-19 pandemic. This research instrument uses 2 (two) measuring instruments, namely General Self Efficacy (GSE) which has been translated into Indonesian and has been modified so that it can be understood by research subjects belonging to Ralf Schwarzer et al. from Freie University, Berlin (2002) and the Utrecht Work Engagement Scale. (UWES) by Bekker and Leiter (2010). The data analysis technique in this study used the Pearson product-moment correlation test; there was a positive and significant correlation between self-efficacy and work engagement with a correlation coefficient of 0.405 with a significance value of 0.002 (p < 0.005). This means that the higher the level of self-efficacy, the higher the work engagement. Conversely, the lower the level of self-efficacy, the lower the level of work engagement that is owned. The results of this study can be used as a basis for activities to increase work engagement to achieve maximum performance for the success of the organization or company.